Leadership in Action: Seven Common Beliefs About Teams: Are They True? - Hallam, Glenn (Center for Creative Leadership, 1997)
Glenn L. Hallam is a research scientist at CCL in Colorado Springs. He has looked closely at these beliefs and has found some surprising answers.